Chiral nematic liquid crystals as an alternative filling in photonic crystal fibers - Tefelska, Marzena M.; Woliński, Tomasz R.; Dąbrowski, Roman; Wójcik, Jan (Photonics Letters of Poland, 2010)
Chiral nematic liquid crystals (LCs) are very interesting materials to infiltrate photonic crystal fibers since they are characterized by unique optical properties such as selective Bragg reflection, circular dichroism and optical activity. In this letter first experimental results of chiral nematic LCs-infiltrated photonic crystal fibers are presented. Full Text: PDF References: P. St. J. Russell „Review: Photonic Crystal Fibers” Science 299, 358-362 (2003). [CrossRef] C. Knight, “Photonic crystal fibres”, Nature 424, 847-851 (2003). [CrossRef] F. Du, Y. Q. Lu, and S. T. Wu, Electrically tunable liquid-crystal photonic crystal fiber, Appl. Phys. Lett. 85, 2181–2183 (2004). [CrossRef] T. Alkeskjold, J. Lægsgaard, A. Bjarklev, D. Hermann, A. Anawati, J. Broeng, J. Li, and S.-T. Wu, All-optical modulation in dye-doped nematic liquid crystal photonic bandgap fibers. Opt. Express 12, 5857–5871 (2004). [CrossRef] T. R. Woliński et al., Meas. Sci. Technol. 17, 985-991 (2006). [CrossRef] T.T. Larsen, A. Bjarklev, D.S. Hermann, and J. Broeng, “Optical devices based on liquid crystal photonic bandgap”, Opt. Express 11, 2589–2596 (2003). [CrossRef] T. R. Woliński, S. Ertman, P. Lesiak, A. W. Domański, A. Czapla, R. Dąbrowski, E. Nowinowski-Kruszelnicki, and J. Wójcik, „Photonic liquid crystal fibers – a new challenge for fiber optics and liquid crystals photonics”, Opto-Electronics Review 14, 329-334, (2006). [CrossRef] T. R. Woliński, A. Czapla, S. Ertman, M.Tefelska, A. W. Domański, E. Nowinowski-Kruszelnicki, R. Dąbrowski, „Tunable highly birefringent solid-core photonic liquid crystal fibers”, Opt. Quantum Electron. 39, 1021-1032 (2007). [CrossRef] T.R. Wolinski, K. Szaniawska, S. Ertman, P. Lesiak, A. W. Domanski, R. Dabrowski, E. Nowinowski-Kruszelnicki and J. Wojcik "Influence of temperature and electrical fields on propagation properties of photonic liquid-crystal fibres", Meas. Sci. Technol. 17, 985–991 (2006). [CrossRef]